Child-Friendly Communication - Váradi-Csema, Erika (Interdisciplinary and Child-Friendly Communication, 2025)
Children’s first encounter with any authority is particularly significant in several respects. Professionals represent adult society, which has typically given minors negative experiences, whether they are perpetrators or victims. At the international level, there has been a growing demand for professionals working in various institutions and dealing with minors to choose a form of communication that meets the needs of the target group. The aim of this chapter is to provide a brief overview of the importance of child-friendly communication and certain aspects of the issue. It focuses on the elaboration of the content elements of two important children’s rights: the right to be heard and the right to express an opinion. When communicating with children, it is important to identify and recognize their specific needs and requirements. The following chapters of the book provide a more detailed overview of child-friendly justice as a whole. This chapter also presents some examples of good practice.Keywords: child-friendly communication, children rights, right to be heard, right to free expression